Desain Macromedia Flash 8 Berbasis Literasi Sains Pada Materi Elektrolit dan Non Elektrolit - Nelson Miyoka; Nurhayati Rusdi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research was instigated by student difficulty in comprehending abstract chemistry lessons, so it was needed an instructional media that could visualize the abstract chemistry to the students. This research aimed at designing scientific literacy-based chemistry instructional media, then validating and testing would be done. In this research, chemistry instructional media was designed by using Macromedia Flash 8 software to support the study on Electrolyte and Non-Electrolyte lesson. The final product result was in the form of a valid instructional media. It was a Research and Development (R&D) with Borg and Gall modified model and it was administered at State Senior High School 5 Pekanbaru. Interview, library study, and questionnaire were the techniques of collecting the data. Scientific literacy-based Macromedia Flash 8 that was developed was tested, it was valid with 86.31% percentage (very valid) and practical with 92% percentage (very practical). It got good responses of all media contents with 30% percentage (very good) and 60% percentage (good). Based on these findings, it could be concluded that scientific literacy-based chemistry instructional media using Macromedia Flash 8 on Electrolyte and Non-Electrolyte lesson was valid, practical, and able to get good responses from students, so it could be experimented at the next stage.